Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2020
DOI: 10.1002/jbmr.4442
|View full text |Cite
|
Sign up to set email alerts
|

A Validated Risk Prediction Model for Bone Fragility in Children With Acute Lymphoblastic Leukemia

Abstract: Although bone fragility may already be present at diagnosis of pediatric acute lymphoblastic leukemia (ALL), routine performance of dual-energy X-ray absorptiometry (DXA) in every child is not universally feasible. The aim of this study was to develop and validate a risk prediction model for low lumbar spine bone mineral density (LS BMD Z-score ≤ À2.0) at diagnosis, as an important indicator for fracture risk and further treatment-related BMD aggravation. Children with ALL (4-18 years), treated according to th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 42 publications
0
4
0
Order By: Relevance
“…A recent Dutch-Canadian collaborative study has demonstrated the predictive value of age and weight at diagnosis in relation to LS aBMD and to subsequent development of symptomatic fractures in children with ALL, 43 complementing our established practice of HAW correction of Z scores for aBMD of the lumbar spine. 27 The results of bone morphometry and measures of bone strength, determined by peripheral quantitative computed tomography (pQCT) 44 in our study of long-term survivors of ALL (more than 10 y from diagnosis), have been reported separately.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…A recent Dutch-Canadian collaborative study has demonstrated the predictive value of age and weight at diagnosis in relation to LS aBMD and to subsequent development of symptomatic fractures in children with ALL, 43 complementing our established practice of HAW correction of Z scores for aBMD of the lumbar spine. 27 The results of bone morphometry and measures of bone strength, determined by peripheral quantitative computed tomography (pQCT) 44 in our study of long-term survivors of ALL (more than 10 y from diagnosis), have been reported separately.…”
Section: Discussionmentioning
confidence: 95%
“…The results in the small number of subjects (n=9) reported here, who were studied more than a decade after diagnosis, are intriguing, being suggestive of late improvement in LS aBMD, but longitudinal examination of a larger cohort will be required to evaluate this observation. A recent Dutch-Canadian collaborative study has demonstrated the predictive value of age and weight at diagnosis in relation to LS aBMD and to subsequent development of symptomatic fractures in children with ALL,43 complementing our established practice of HAW correction of Z scores for aBMD of the lumbar spine 27…”
Section: Discussionmentioning
confidence: 99%
“…Future fractures are substantially predicted by VFs in the first two years following diagnosis. In order to identify asymptomatic VFs, forecast future fracture risk, prevent vertebral abnormalities, and reduce long-term morbidity, lateral spine imaging is advised for up to 45% of children with VFs [18]. A paediatric bone specialist must monitor Duchenne muscular dystrophy patients due to immobility, extended steroid use, and hypogonadism [19].…”
Section: Secondary Osteoporosismentioning
confidence: 99%
“…The risk of fractures is the highest in the first two years of diagnosis and the presence of VFs at diagnosis is highly predictive of future fractures. Up to 45% of children presenting with VFs at the diagnosis can be asymptomatic; therefore, lateral spine imaging is advised to detect asymptomatic VFs, predict the risk of future fractures, and prevent vertebral deformities and long-term morbidity [ 58 60 ].…”
Section: Secondary Osteoporosismentioning
confidence: 99%